ANALYTICAL SUPPORT FOR MANAGING THE EFFICIENCY OF ENTERPRISES - В. Ю. Дудник (Ekonomìčnij Vìsnik Nacìonalʹnogo Tehnìčnogo Unìversitetu Ukraïni "Kiïvsʹkij Polìtehnìčnij Institut")
In modern conditions, enterprises face numerous challenges that require improved management efficiency and resource optimization. Ensuring balanced development and competitiveness of enterprises necessitates the implementation of modern management approaches based on in-depth activity analysis and effective decision-making. This article examines the role of analytical support in management in the context of enhancing strategic planning, monitoring key performance indicators, and implementing resource optimization measures. Special attention is given to approaches for integrating analytical tools into management practices to streamline costs, increase productivity, and adapt enterprises to changes in the external environment. The analysis highlights the impact of these tools on the quality of managerial decisions and their role in ensuring sustainable development. The article also provides practical recommendations for integrating analytical support systems into management processes to enhance transparency, operational efficiency, and long-term competitiveness of enterprises. The study is based on a theoretical analysis of modern approaches to enterprise efficiency management and practical findings that demonstrate the effectiveness of analytical support in today's business environment.